2021
DOI: 10.1002/jcop.22724
|View full text |Cite
|
Sign up to set email alerts
|

“Halfway Independent”: Experiences of formerly homeless adults living in permanent supportive housing

Abstract: Permanent supportive housing (PSH), which combines affordable public housing with social services, has become the dominant model in the United States for providing housing to formerly homeless people. PSH has been effective in reducing re‐entry to homelessness, yet has shown limited evidence of improving formerly homeless individuals' mental health and quality of life. This study aimed to understand the lived experiences of formerly homeless adults' adjustment to tenancy in PSH, with a focus on how living in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Congregate PSH has been shown to reduce social isolation and to provide a more comprehensive response to resident needs compared with other models [27], while also allowing for day-to-day interactions between staff and residents [28], which increased the ability to identify emerging problems [29]. Social participation has also been linked to higher QoL [30,31]. Yet, the advantages in congregate PSH of sharing living spaces with peers, and having staff onsite, may have been offset by greater isolation from the outside world during the COVID-19 pandemic, as reported in long-term care residences for the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Congregate PSH has been shown to reduce social isolation and to provide a more comprehensive response to resident needs compared with other models [27], while also allowing for day-to-day interactions between staff and residents [28], which increased the ability to identify emerging problems [29]. Social participation has also been linked to higher QoL [30,31]. Yet, the advantages in congregate PSH of sharing living spaces with peers, and having staff onsite, may have been offset by greater isolation from the outside world during the COVID-19 pandemic, as reported in long-term care residences for the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the advantages in congregate PSH of sharing living spaces with peers, and having staff onsite, may have been offset by greater isolation from the outside world during the COVID-19 pandemic, as reported in long-term care residences for the elderly. General regulations about prohibition related to home visits and travelling during the pandemic may also have affected equally the two PSH groups [30]. Concerning duration of residence in PSH, a recent systematic review demonstrated that PSH have sustained greater housing stability and more long-term benefits than treatment as usual but not for QoL in follow-up data up to 6 years [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, most LEG members have previously been involved in activities—such as volunteering for research projects, speaking at conferences, or working as peer advocates in PSH programs—that are not typically pursued by most people who experience homelessness. Many individuals exiting homelessness continue to experience a lack of meaningful activity and social integration, (Harris et al, 2019 ; Hawkins & Abrams, 2007 ; Pilla & Park-Taylor, 2022 ), and it is likely that that our LEG members are more active and engaged in their community than most people who are experiencing homelessness or transitioning to housing. Furthermore, in our study, lived experience contributions were confined to the perspectives of people who had previously experienced homelessness.…”
Section: Considerations For Future Collaborationmentioning
confidence: 99%
“…The COVID-19 pandemic opened a window to comprehensively examine the diverse vulnerabilities regarding homeless individuals, including physical health (Kar et al, 2020), mental health (Martin et al, 2021), overall wellbeing (van Ruth, 2021), vaccine hesitancy (Balut et al, 2021), historical poverty and alterative affordable housing (Pilla & Park-Taylor, 2021), and social exclusions (Platt et al, 2021), with a focus on the entire life span from youth (Schwan et al, 2020) to older adults (Gombita et al, 2020). When governments worldwide released stay-athome orders to quickly respond to the COVID-19 emergency, previous housing challenges faced by homeless individuals were compounded by the public health protocols, further strengthening their vulnerabilities and related negative influence as well as reducing their coping capacities of developing mitigation strategies (Obasi & Anierobi, 2020;Wu & Karabanow, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%